Associations of vitamin D status and vitamin D-related polymorphisms with sex hormones in older men. Issue 164 (November 2016) - Rafiq, R.; van Schoor, N.M.; Sohl, E.; Zillikens, M.C.; Oosterwerff, M.M.; Schaap, L.; Lips, P.; de Jongh, R.T.
Highlights: Vitamin D might influence sex hormone and gonadotropin levels. We studied relationships between 25(OH)D, gene polymorphisms and sex hormone levels. Lower vitamin D status is associated with lower testosterone levels. There was no association between gene polymorphisms and sex hormone levels. Abstract: Objective: Evidence regarding relationships of serum 25-hydroxyvitamin D (25(OH)D) with sex hormones and gonadotropin concentrations remains inconsistent. Polymorphisms in vitamin D-related genes may underly these relationships. Our aim was to examine the relationship of vitamin D status and polymorphisms in vitamin D-related genes with sex hormone and gonadotropin levels. Design and measurements: We analysed data from the Longitudinal Aging Study Amsterdam, an ongoing population-based cohort study of older Dutch individuals (65–89 years). We included data of men with measurements of serum 25-hydroxyvitamin D (25(OH)D) ( n = 643) and determination of vitamin D-related gene polymorphisms ( n = 459). 25(OH)D concentrations were classified into four categories: <25, 25–50, 50–75 and >75 nmol/L. Outcome measures were total testosterone, calculated bioavailable and free fraction testosterone, SHBG, estradiol, LH and FSH concentrations. Hypogonadism was defined as a total testosterone level <8.0 nmol/L. Results: Serum 25(OH)D was positively associated with total and bioavailable testosterone levels. After adjustments for confounders, men with serum 25(OH)D less than 25 ( n = 56), 25–50 ( n = 199) and 50–75 nmol/L ( n = 240) had lower total testosterone levels compared to men with serum 25(OH)D higher than 75 nmol/L ( n = 148) (β (95% confidence interval): −2.1 (−3.7 to −0.4 nmol/L), −0.8 (−1.9 to 0.4 nmol/L) and −1.4 (−2.4 to −0.3 nmol/L), respectively). For bioavailable testosterone the association was significant only for men with serum 25(OH)D less than 25 nmol/L (−0.8 (−1.4 to −0.1 nmol/L)) compared to men with serum 25(OH)D >75 nmol/L. Serum 25(OH)D was not related to SHBG, estradiol or gonadotropin levels. Hypogonadism ( n = 29) was not associated with lower serum 25(OH)D. No significant differences were found in hormone levels between the different genotypes of the vitamin D-related gene polymorphisms. Also, the polymorphisms did not modify the relationships of serum 25(OH)D with sex hormones or gonadotropins. Conclusion: Vitamin D status is positively associated with testosterone levels. No association was found between vitamin D-related gene polymorphisms and hormone levels.